Communicational and lobbying power in German farm animal welfare politics - Michael Grunenberg; Christian H. C. A. Henning (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2019)
Farm animal welfare is the main driver of nowadays criticism on German livestock sector. At the same time, non market actors more and more are key actors within animal welfare politics. Hence, we investigate political power of stakeholder organizations in German livestock policy. Our network based framework consists of two components: First, actors influence policy decisions through informational lobbying. Informational lobbying refers to providing expert knowledge in order to influence decision makers' policy beliefs. Second, the exchange of influence resources and power allows interest groups to influence the policy positions of political agents. We combine both measurements with the Banzhaf power index in order to quantify the power of both, political agents as well as interest groups. How this power affects animal welfare policy is illustrated in the field of piglet castration. Results imply that the agricultural sector as well as animal protection groups have the highest influence on beliefs and that state actors distribute most of the power to the agribusiness sector. This structures leads to a positive evaluation of surgical castration under anaesthesia. On the other hand, immunocastration is evaluated as rather useless. This implies that participatory processes decrease the procedures acceptance.
Keywords: 330; communicational lobbying; political support; stakeholder influence; farm animal welfare